Evaluation of Interleukin -1β, GOT, and GPT in Patients with Giardiasis in Thi-Qar Province - Al-musawy, Fatima Assad Baker; Hussein, Murtada Hafedh (University of Thi-Qar Journal of Science, 2022)
Giardiasis is a well-known gastroenteritis that causes small intestine malabsorption and fatty diarrhea. The current study was performed from the start of September 2021 to the end of March 2022. Fifty blood samples were collected from suspected infected patients with G. lamblia when they returned to the laboratory to receive the result of microscopic analysis and were proved to be infected with the parasite, and (40) blood samples were collected from healthy people as a control group. This study reveals a significant increase in the level of interleukin-1B, being (2.807) in the infected patients. Higher than in the control group (0.454). The study of biochemical parameters of patients infected with parasites showed an increase in the concentration of liver enzymes (GOT and GPT) in patients and compared to the healthy group